(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
This article provides a scholarly analysis of toponyms as products of human intellectual, cognitive, and discursive activity. The phenomenon of onomastic transfer is interpreted as a speech process, and the semantic, onomasiological, and cognitive mechanisms involved in object naming are identified. The processes of appellativization of proper names and onymization of common nouns are examined as manifestations of the intrinsic relationship between language and speech units. The formation of natural and artificial nominations is demonstrated through the interaction between toponyms and appellative units in connection with the semantic sources of geographical names. Toponymic lexis is evaluated from cognitive and ethnolinguistic perspectives, substantiating its status as one of the most significant layers of language reflecting collective thinking, historical memory, and cultural experience.